New Triangular Vlc Cell Plus Protocol to Uplink the Data in Vsat/Gps Format - Soto-Gomez, J; San Juan-Urrutia, E; Adasme-Soto, P (Institute of Electrical and Electronics Engineers Inc., 2019)
The purpose of this document is to present a new triangular VLC cell and a new protocol to upload the data in GPS format to a remote control station, for the supervision of a person or device in an underground tunnel. Trilateration and calibration studies of a VSAT satellite signal are carried out. In addition, the performance studies of the solution are presented. © 2019 IEEE.